THE HEGEMONY OF KEYBOARD DEFAULTS - Zaugg, Isabelle Alice; Reeve, Jonathan (AoIR Selected Papers of Internet Research, 2021)
No single tool is more fundamental to writing—and more unexamined—than the computer keyboard. Most of us in the West never consider that the standard QWERTY key layout, i.e. the staggered key design and the selection of keys available, is anything but the received, traditional means of text input. And as such, keyboard/device manufacturers wield a unique form of power: they dictate the kind of words we can create. They further decide, however unconsciously, the motions our fingers take when we write; the staggered layout was necessary for the proper functioning of mechanical typewriters, but has no necessity for computers (let alone mobile devices), yet continues to be replicated, despite the fact that it is responsible for repetitive stress injuries that could be eliminated or reduced with an improved ergonomic design. QWERTY may even shape the meaning of words that we type. Furthermore, considering the global reach of QWERTY against the backdrop of language diversity, and particularly the approximately 300 non-Latin scripts in existence, the hegemony of default QWERTY keyboards hints at the ongoing impacts of the colonial legacy within digital technologies. Thus, to make computing, and the Internet, more equitable and humane, we must reimagine our keyboard layouts, the characters they include, and our modes of human-computer interaction. Our paper presents this case, employing data analyses of hardware and software keyboard usage statistics.